Analysis of Indonesian Exports Demand in the ASEAN Region - Taosige Wau (Economics Development Analysis Journal, 2023)
The dynamics of a country's exports are determined not only by the supply side but also by the demand side. This research examines the influence of the demand side on Indonesia's exports. Its primary aim is to analyze the effects of per capita income, inflation, and the exchange rates of partner countries on the demand for Indonesia's exports in the ASEAN region. The data used is panel data covering the observation period from 2000 to 2021, encompassing nine ASEAN member countries trading partners with Indonesia. The analytical method employed is a panel regression model using a random effects approach, estimated through the EGLS method. The findings indicate that an increase in per capita income, inflation, and the appreciation of partner countries' currencies against the USD can stimulate the demand for Indonesia's exports in the ASEAN region, albeit to varying degrees.